The Role of Illustrated Digital Storybooks in Supporting Second Language Acquisition: A Qualitative Analysis Using the Let’s Read App - Ilham Devara Hendar Putra; Pratiwi Retnaningdyah; Ali Mustofa; Lies Amin Lestari (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study investigates the role of illustrated digital storybooks in supporting Second Language Acquisition (SLA) in young learner, with a specific focus on the Let’s Read app. By exploring how engaging visuals and interactive storytelling influence motivation, engagement, and vocabulary acquisition, the research highlights the effectiveness of multimodal learning in SLA. Through an in-depth interview with young learner, the study reveals that illustrations in digital storybooks not only enhance comprehension but also maintain learner interest and curiosity, aligning with Krashen’s Input Hypothesis (1982) and Vygotsky’s theories of social interaction in language learning. Furthermore, the study emphasises the app’s ability to offer an organised, and age-appropriate environment, making it an effective tool for fostering language development. This research contributes to the growing body of literature on digital tools in SLA and suggests the integration of such resources into educational practices in order to support holistic language learning in the digital age.